CRISPRe: An innate transcriptional enhancer for endogenous genes in CRISPR-Cas immunity - Dan Li; Yihong Chen; Fei Huang; Jianmei Wang; Xufeng Li; Yi Yang (iScience, 2023)
Summary: CRISPR-Cas system has been repurposed to the promising strategy of CRISPR-based transcriptional interference/activation (CRISPRi/CRISPRa) without eliciting DNA breaks that enables Cas complex a block for transcription initiation or elongation, which greatly expands its application fields and values. However, loss of Cas nuclease ability, especially the endogenous nuclease, may affect genome stability seriously. Here, we found a transcriptional enhancer for genes (CRISPRe) in type I-C system of industrial strain Ketogulonicigenium vulgare by maintaining the natural activity of Cas3 nuclease and introducing the specific motifs that do not trigger immunity. CRISPRe greatly improved the expression of heterologous and endogenous genes and the biosynthesis of products by facilitating transcriptional elongation. Besides, the mechanism for pyrroloquinoline quinone (PQQ) biosynthesis regulated by coupling transcriptional-translational elongation in operon was elucidated. Hence, we enrich the toolbox for CRISPR-Cas system and provide a new framework for gene regulation at transcription.